A sampling method for the reconstruction of a periodic interface in a layered medium. (18th May 2016) - Sun, Guanying; Zhang, Ruming
Abstract: In this paper, we consider the inverse problem of reconstructing periodic interfaces in a two-layered medium with TM-mode. We propose a sampling-type method to recover the top periodic interface from the near-field data measured on a straight line above the total structure. Finally, numerical experiments are illustrated to show the effectiveness of the method.